Exploring chamazulene as a novel therapeutic agent for breast cancer in silico and in vitro: apoptosis induction, cell cycle regulation, and antimetastatic effects - Yao, Liang; Wang, Wanfu; Zhang, Bo (Frontiers in Pharmacology, 2025)
ObjectivesThis study used a combination of in silico and in-vitro methodologies to evaluate the breast cancer (BC) fighting efficacy of Chamazulene.MethodsIn silico analyses utilized Protox-3.0 for toxicity prediction, SuperPred and GeneCards for target identification, and Jvenn for intersection. Protein–protein interactions were mapped with STRING and visualised in Cytoscape, followed by Cytohubba to pinpoint hub genes. Gene-ontology and KEGG-pathway enrichment were performed via DAVID and visualized with SRplot. Immune infiltration was assessed using TIMER, while UALCAN evaluated expression, promoter methylation, survival, and correlation. The MTT, clonogenic, EdU, Annexin-V/PI, cell cycle, wound healing, and Western-blotting were used to measure cytotoxicity and the mechanism of chamazulene in MDA-MB-231 cells.ResultsIn silico analyses indicated a safe toxicity profile and identified 53-overlapping target genes, resulting in a highly enriched PPI network. The network identified the three main hub genes: NFKB1, MAPK14, and GRB2. Enrichment analysis indicated participation in different pathways, including MAPK and HIF-1 signalling pathways. The TIMER and UALCAN investigations on BC revealed significant immune infiltration, altered gene expression, hypomethylation, and survival trends. MTT studies demonstrated a dose-dependent reduction in cancer cell viability, exceeding 50% at elevated doses. Clonogenic and EdU assays indicated reduced proliferation and DNA-synthesis, whereas apoptosis and cell cycle analyses revealed elevated cell mortality and G2/M-phase arrest. Western blotting revealed a downregulation of NFKB1, GRB2 and MAPK14, while wound healing assays suggested reduced migration.ConclusionChamazulene exhibits multifaceted and potent anticancer effects by specifically modifying crucial signalling-pathways and processes in aggressive BC, warranting preclinical studies to validate its therapeutic potential.